Management of polycystic ovary syndrome with arcuate uterus through individualized homoeopathy: a case report - Karmakar, Dibakar; Das, Arnab R.; Parui, Patranu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy among reproductive-aged women. It is manifested by irregular menstrual cycles, polycystic ovaries, acne, excess unwanted hair growth, obesity, etc. PCOS can affect a female’s fertility. This was a case of 22 years female suffering from PCOS reported here was treated successfully within 1 year by a single individualised homoeopathic medicine Pulsatilla in centesimal potency with repetition as per requirement. The improvement is evident from regularity of menstrual cycle and also from the ultrasonography (USG) reports. Modified Naranjo criteria for homoeopathy score (+8 on the ‘−6–+13’ scale) proved the causal attribution between the homoeopathic medicine and the outcome in the patient. This case study reveals a certain role of homoeopathic treatment in PCOS and demonstrates the potential of homoeopathy in this type of conditions.